Bauhinia acuminata L. attenuates lung cancer cell proliferation: in vitro, in vivo and in silico approaches - Divya Sebastian; K. Gowri Shankar; S. Ignacimuthu; A.J. Renilda Sophy; R. Vidhya; J.R. Anusha (Elsevier, 2022)
Background: The present study aims to explore the efficacy and suitability of Bauhinia acuminata L. to attenuate lung cancer on in vitro lung cancer cell lines, in vivo benzo(a)pyrene (BaP) induced mice model and in silico molecular docking. Methods: Both in vitro and in vivo models were used to assess the efficacy of chloroform crude extracts of B. acuminata (CEBA) leaves fractions. For in vitro cytotoxicity analysis, A549 and Vero cancer cell lines were used. The BaP treated and untreated C57BL/6 mice were grouped and the in vivo acute toxicity levels were analyzed. Ethyl acetate (EA) fraction of CEBA was orally administrated in BaP treated mice and various parameters were measured in serum, liver, lung and kidney tissues. In addition, the histological, enzymatic, immunohistochemical, p53 expression and in silico molecular docking was carried out. Results: CEBA was found to be cytotoxic against lung cancer cell lines. The oral administration of CEBA revealed good anti-lung cancer potential in BaP induced lung cancer mice. The enzymatic and non-enzymatic antioxidants level significantly increased after the treatment of CEBA. In addition, the biochemical and histological parameters were normal in CEBA treated animals. The molecular docking showed good binding between ligands of ethyl acetate fraction and the receptors of lung. Conclusion: This study confirmed the anti-proliferative capability of ethyl acetate fraction of chloroform extract of B. acuminata on lung cancer models. These findings may represent a promising candidate for cancer therapy and used for further investigations in the clinical studies.